Association between possible sarcopenia, peripheral neuropathy, and the risk of falls in patients with type 2 diabetes mellitus - Hangsaphruek, Surapa; Jongutchariya, Thitirut; Wongkiratimethawi, Thaweesak; Nualyam, Areerat; Trapsinsaree, Doungmon (Journal of Medicine and Health Sciences, 2025)
Type 2 diabetes is a health problem that affects various systems of the body, especially the muscular and nervous systems. Sarcopenia is common in diabetic patients and may increase the risk of peripheral neuropathy and falls, which affect quality of life and can lead to serious complications. This retrospective study aimed to study the relationship between possible sarcopenia peripheral neuropathy and the risk of falls in patients with type 2 diabetes. The sample consisted of 455 patients diagnosed with type 2 diabetes for 5 years or more and were aged 50 years or older and received treatment between October 1, 2023 and September 30, 2024. The study used medical record review and statistical data analysis using ready-made programs, including frequency, percentage, mean, standard deviation, and analysis of the relationship using Pearson Chi-square, Fisher's exact test, and Multiple logistic regression. The results showed that 31.6% of the patients had sarcopenia, 17.8% had neuropathy, and 47.5% were at risk of falls. Sarcopenia was associated with neurological deficits (p = 0.014) and falls risk (p < 0.001). Multiple logistic regression analysis showed that those with sarcopenia were approximately 2.11 times more likely to fall than those without sarcopenia (OR = 2.11; 95% CI: 1.26, 3.55; p =0.005). Therefore, surveillance and development of preventive measures, such as exercise and nutritional care, are important to reduce the risk and improve the quality of life of patients. These findings support the integration of sarcopenia screening into routine diabetes care to reduce fall risk.